Assessment of acute motor deficit in the pediatric emergency room - Marcio Moacyr Vasconcelos; Luciana G.A. Vasconcelos; Adriana Rocha Brito (Jornal de Pediatria (Versão em Português), 2017)
Objectives: This review article aimed to present a clinical approach, emphasizing the diagnostic investigation, to children and adolescents who present in the emergency room with acute‐onset muscle weakness. Sources: A systematic search was performed in PubMed database during April and May 2017, using the following search terms in various combinations: “acute,” “weakness,” “motor deficit,” “flaccid paralysis,” “child,” “pediatric,” and “emergency”. The articles chosen for this review were published over the past ten years, from 1997 through 2017. This study assessed the pediatric age range, from 0 to 18 years. Summary of the data: Acute motor deficit is fairly common presentation in the pediatric emergency room. Patients may be categorized as having localized or diffuse motor impairment, and a precise description of clinical features is essential in order to allow a complete differential diagnosis. The two most common causes of acute flaccid paralysis in the pediatric emergency room are Guillain‐Barré syndrome and transverse myelitis; notwithstanding, other etiologies should be considered, such as acute disseminated encephalomyelitis, infectious myelitis, myasthenia gravis, stroke, alternating hemiplegia of childhood, periodic paralyses, brainstem encephalitis, and functional muscle weakness. Algorithms for acute localized or diffuse weakness investigation in the emergency setting are also presented. Conclusions: The clinical skills to obtain a complete history and to perform a detailed physical examination are emphasized. An organized, logical, and stepwise diagnostic and therapeutic management is essential to eventually restore patient's well‐being and full health.